2016
DOI: 10.1016/s2213-8587(16)30156-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of renal function on the effects of LDL cholesterol lowering with statin-based regimens: a meta-analysis of individual participant data from 28 randomised trials

Abstract: UK Medical Research Council, British Heart Foundation, Cancer Research UK, European Community Biomed Programme, Australian National Health and Medical Research Council, Australian National Heart Foundation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
111
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(117 citation statements)
references
References 63 publications
1
111
0
5
Order By: Relevance
“…Studies have indicated that long-term use of statins can improve the initial clinical symptoms of ACS patients and reduce the incidence of ST segment elevation myocardial infarction1415. Different retrospective studies and meta-analysis have shown that for patients undergoing elective PCI, statin therapy can effectively reduce the incidence of postoperative PMI161718. A large number of studies have shown that, in addition to stable plaque, statins can improve endothelial function and anti-inflammatory and improve the vascular wall inflammation induced by PCI.…”
mentioning
confidence: 99%
“…Studies have indicated that long-term use of statins can improve the initial clinical symptoms of ACS patients and reduce the incidence of ST segment elevation myocardial infarction1415. Different retrospective studies and meta-analysis have shown that for patients undergoing elective PCI, statin therapy can effectively reduce the incidence of postoperative PMI161718. A large number of studies have shown that, in addition to stable plaque, statins can improve endothelial function and anti-inflammatory and improve the vascular wall inflammation induced by PCI.…”
mentioning
confidence: 99%
“…Highly credible evidence from RCTs also showed that statin use was associated with lower all-cause mortality in CKD patients not on dialysis, but the association was not significant in patients undergoing dialysis. An individual patient data meta-analysis also showed that there were trends for relatively smaller cardiovascular and all-cause mortality benefits of statins as eGFR declined [53]. The benefit of statin use in CKD patients not on dialysis was also acknowledged by current guidelines [11,54,55].…”
Section: Discussionmentioning
confidence: 98%
“…On the one hand, meta-analyses [14, 36] have shown that lowering LDL-C with statin therapy could effectively reduce vascular risk among patients with mild-to-moderate CKD and delay the progress of CKD. On the other hand, the pleiotropic effects of statins [37-39], which included reducing free radical levels, increasing endothelial nitric oxide synthase levels and inhibiting the activity of excitotoxic amino acids and the production of inflammatory mediators, could also decrease common risk factors of CKD and cerebrovascular diseases [40] (e.g., oxidative stress and inflammation).…”
Section: Discussionmentioning
confidence: 99%
“…Statins are also recommended for the primary and secondary prevention of cerebrovascular diseases [8, 9]. Recently, many studies focused on the efficiency of statin use in patients with CKD [10-14]. Previous studies showed that statin use had a relationship with decreased mortality of patients with myocardial infarction (MI) and mild-to-severe renal insufficiency for secondary prevention [10, 11].…”
Section: Introductionmentioning
confidence: 99%